Pencegahan Tindakan Bullying Pada Anak Usia Dini Berbasis Penguatan Nilai Agama Dan Moral - Ali, Musyafa; Prawening, Cesilia (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Agama Islam Universitas Nahdlatul Ulama Purwokerto, 2024)
Cases of violence against children are one of the highlights in the world of education in Indonesia, the rise of cases of violence against children raises various problems. The purpose of this study is to describe and analyze how to prevent bullying in early childhood on the basis of strengthening religious and moral values in children. This research was conducted at the RA of the Wadas Kelir Creative House. This type of research is a field research using a qualitative approach. Data collection is carried out by observation, interview, and documentation techniques. Data analysis techniques are carried out by means of data reduction, data presentation, verification and conclusion drawn. The results of this study show that the things done by teachers to prevent bullying in early childhood by strengthening religious and moral values are through worship activities (memorizing asmaul husn and reading Islamic stories), habituation (respecting each other, telling the truth, helping, and respecting each other), and role models (Do not speak harshly, do not compare, be fair, and do not use punches to punish). The impact of the activities carried out on the child's attitude is an attitude of mutual respect, high empathy, and self-confidence.